STRATEGI PENGEMBANGAN USAHA PERKEBUNAN KELAPA SAWIT RAKYAT DI DESA TIKKE KECAMATAN TIKKE RAYA KABUPATEN PASANGKAYU - Aulia, Sinar; Mappatoba, Marhawati; Abubakar, Ihdiani (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
Tikke, a village located in Tikke Raya Sub District of Pasangkayu District, is primarily inhabited by oil palm farmers. This study aimed to determine appropriate alternative strategies to be implemented in the development of smallholder oil palm plantations in the village. Respondents were purposively selected, resulting in a total of 30 participants, comprising 25 oil palm plantation owners, two workers, two collectors, and one representative from the Plantation and Livestock Service Office of Pasangkayu District. SWOT analysis was used in this research to calculate the internal and external factors scores. The factor scores were 1.46 for the internal factors and 1.47 for the external factors indicating that the development strategy for the smallholder oil palm plantation business is in quadrant I and to enhance productivity is through the strengths - opportunities (SO) strategy. The proposed alternative strategies include (i) utilizing ownership certificates as collateral for banking institutions, (ii) leveraging the high morale and productive age of plants to encourage wise technology adoption by farmers, (iii) establishing effective communication channels with the workforce and the company to boost oil palm plantation productivity, and (iv) Increasing productivity by employing local workers, which can contribute to reducing unemployment.